Nexus between Fiscal Discipline and the Budget Process in Africa: Evidence from Nigeria - ADEKUNLE, Wasiu; BEKOE, William; BADMUS, Sheriff; ANAGUN, Adeyemi M.; ALIMI, Wasiu (Theoretical and Practical Research in Economic Fields, 2021)
This paper examined the nexus between fiscal discipline and the budget process in Nigeria over the period from 1990 to 2020. Findings showed that the level of fiscal discipline in Nigeria as measured by two proxies of fiscal deficit gap and public debt gap is more enhanced under zero-based budgeting than under current incremental budgeting system. The study also established that civilian administrations are more prone to fiscal indiscipline relative to military dispensations. The paper also revealed the significant role of net foreign aid receipts in significantly narrowing fiscal deficit and public debt gaps in the short-run and long-run, respectively, as well as noted the significant widening impact of an increasing government size on the public debt gap in the long run. The study recommends, among others, the urgent need for the Nigerian government to restore fiscal discipline in public affairs through a reversion to zero-based budgeting system.